Integración de las tecnologías de información y comunicación en la docencia universitaria para una educación inclusiva - Colina Vargas, Alejandra Mercedes (2018)
The article presented aims to analyze how the integration of ICT in the university curriculum favors the generation of learning in diverse social contexts and emerging cognitive processes. The theoretical referents that supported the research were taken from documentary sources that explain the characteristics of the object of study from different theoretical positions, which allowed us to assume a critical stance that teaches the integration and subsequent appropriation of ICT in university teaching with a vision social and inclusive, where the builder emerges that the appropriation is conceived as the full integration of ICT in the cultural and social context of teachers. From the context presented, it is stated that the teacher has the ability to use ICT to the point of making them important for their daily activities in the classroom and thus generate ICT skills that contribute significantly to the improvement of their living conditions and their social transformation (Hill, 2018). Given this context, it is affirmed that the development of educational inclusion requires a relevant analysis of educational practices with their corresponding processes of transformation, not being reduced as a punctual discourse with a limited time course, since there have been many declared intentions and written regulations that have been implemented in multiple contexts for this educational modality. Finally, a systematization and reflections were reached in the definitions of integration and appropriation of technologies to favor educational inclusion, specifying in the university teacher for being an element of vital importance with a view to contributing to the improvement and preparation of autonomous, critical students of knowledge and society by acquiring professional training